Case Report: Tranexamic Acid-Induced Nausea After Bilateral Concha Reduction Surgery - Maitsa Alya Fakhirah; Gofarana Wilar; Falerina Puspita (Indonesian Journal of Clinical Pharmacy, 2026)
Tranexamic acid (TXA) is an antifibrinolytic agent widely used to control perioperative bleeding, including in otolaryngologic procedures. Although generally well tolerated, gastrointestinal side effects such as nausea are occasionally reported but often overlooked in clinical practice. This case report presents a 32-year-old female who developed nausea following the administration of intravenous TXA after undergoing bilateral concha reduction surgery in a hospital in Bandung, June 2025. The nausea resolved after discontinuation of the drug but recurred with greater intensity upon re-administration the following day. A causality assessment was performed using the Naranjo Adverse Drug Reaction Probability Scale, resulting in a total score of 6, indicating a probable relationship between TXA and the onset of nausea. No alternative causes were identified, and symptoms subsided spontaneously without antiemetic intervention after TXA was discontinued. This clinical observation suggests that repeated administration of TXA may increase the risk or severity of nausea in susceptible patients. The use of a structured causality assessment provided objective support for the adverse drug reaction. This case emphasizes the importance of clinician awareness regarding the potential for TXA-induced nausea, especially in Ear, Nose, and Throat (ENT) surgery, where repeated doses may be required. Moreover, documentation of such cases contributes to strengthening ENT-specific pharmacovigilance and highlights the need for further research into adverse effects associated with TXA in this surgical population.Keywords: adverse effect, case report, Naranjo algorithm, nausea, tranexamic acid Laporan Kasus: Mual Akibat Asam Traneksamat Pasca Operasi Reduksi Konka BilateralAbstrakAsam traneksamat (TXA) adalah agen antifibrinolitik yang banyak digunakan untuk mengendalikan perdarahan perioperatif, termasuk dalam prosedur otolaringologi. Meskipun umumnya ditoleransi dengan baik, efek samping gastrointestinal seperti mual terkadang dilaporkan tetapi sering terabaikan dalam praktik klinis. Laporan kasus ini menyajikan seorang wanita berusia 32 tahun yang mengalami mual setelah pemberian TXA intravena setelah menjalani operasi reduksi konka bilateral di rumah sakit di Bandung, Juni 2025. Mual tersebut mereda setelah penghentian obat tetapi kambuh dengan intensitas yang lebih besar setelah pemberian kembali keesokan harinya. Penilaian kausalitas dilakukan menggunakan Skala Probabilitas Reaksi Obat yang Merugikan Naranjo, menghasilkan skor total 6, yang menunjukkan kemungkinan hubungan antara TXA dan timbulnya mual. Tidak ada penyebab alternatif yang teridentifikasi, dan gejala mereda secara spontan tanpa intervensi antiemetik setelah TXA dihentikan. Observasi klinis ini menunjukkan bahwa pemberian TXA berulang dapat meningkatkan risiko atau keparahan mual pada pasien yang rentan. Penggunaan penilaian kausalitas terstruktur memberikan dukungan objektif terhadap reaksi obat yang merugikan. Kasus ini menekankan pentingnya kesadaran klinisi mengenai potensi mual akibat TXA, terutama pada operasi Telinga, Hidung, dan Tenggorokan (THT), yang mungkin memerlukan dosis berulang. Lebih lanjut, dokumentasi kasus-kasus tersebut berkontribusi pada penguatan farmakovigilans khusus THT dan menyoroti perlunya penelitian lebih lanjut mengenai efek samping yang terkait dengan TXA pada populasi bedah ini.Kata kunci: algoritma Naranjo, asam traneksamat, efek samping, laporan kasus, mual